A measurement criterion for accurate mass detection using vibrating suspended microchannel resonators. (1st September 2017) - Yan, Han; Zhang, Wen-Ming; Jiang, Hui-Ming; Hu, Kai-Ming; Hong, Fang-Jun; Peng, Zhi-Ke; Meng, Guang
Abstract: In this paper, a measurement criterion is presented to ensure the accuracy of mass detection using suspended microchannel resonators. The dynamic characteristics of the microchannel resonator with an added suspended particle are investigated to analyze and clarify the measurement principle for mass detection. It indicates that the vibration properties of the suspended particle have a significant effect on the measurement accuracy and the generation of systematic error. The fluid-structure interaction vibration of the particle driven by the resonator is solved by the lattice Boltzmann method integrated with the immersed boundary method. The effects of several important factors, including the particle density, fluid viscosity, and oscillating frequency, are studied and discussed. The results demonstrate that the Reynolds number and the density ratio are the two crucial parameters which affect the measurement accuracy and error generation. As the Reynolds number or the density ratio increases, the measurement precision degrades. Moreover, once the Reynolds number decreases to a critical value, the systematic error of mass detection reduces to zero. The measurement criterion can be taken as the guide to accurately detect the mass of suspended particle in the resonator.